Spectroscopic and molecular modeling studies on the interaction of tyrosine kinase inhibitors with human serum albumin / Md. Zahirul Kabir - Md. Zahirul , Kabir (2018)
Targeted therapies, involving new class drug molecules have shown inhibitory activities against signaling pathways that are responsible for triggering various carcinomas. Tyrosine kinases form an important class of enzymes of these signaling pathways and can be a useful target to develop effective therapeutic agents as tyrosine kinase inhibitors to treat various cancers. Some of the FDA-approved drug molecules, known as tyrosine kinase inhibitors are vandetanib (VDB), lapatinib (LAP), gefitinib (GEF) and sunitinib (SU), which are currently being used for the treatment of medullary thyroid, breast, lung and renal cancers, respectively. Interaction mechanisms of VDB, LAP, GEF and SU binding to human serum albumin (HSA), the major transport protein in the human blood circulation were explored using various spectroscopic techniques such as fluorescence, absorption and circular dichroism (CD) along with in silico studies. Quenching of the protein fluorescence upon addition of these ligands was characterized as the static quenching, which confirmed the complex formation between the ligand and the protein. Such complex formation was also affirmed by absorption spectral results. Moderate binding affinity for these interactions was evident from the binding constant (Ka) values, obtained at 298 K, which had fallen in the range of 104– 105 M–1 except VDB–HSA interaction, which showed relatively weaker binding affinity. Thermodynamic data for the binding equilibria predicted involvement of hydrophobic and van der Waals interactions along with hydrogen bonds in stabilizing drug–HSA complexes, which was also supported by molecular docking results. The far- UV and the near-UV CD spectra showed changes in the secondary and the tertiary structures, respectively, of HSA upon ligand binding. Three-dimensional fluorescence spectral results also indicated ligand-induced microenvironmental perturbations around protein fluorophores. Binding of these ligands to HSA offered significant protection to the protein against thermal denaturation. Competitive site-marker displacement results as well as molecular docking analyses revealed preferred binding location of these drug molecules primarily at site I for VDB and SU while at site III for LAP and GEF, located in subdomains IIA and IB, respectively, of HSA. The influence of a few common ions on the binding reaction between the ligand and HSA was also noticed.